2023
DOI: 10.3389/fnagi.2023.1103039
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of antidepressant therapy for the agitation of dementia: A systematic review and network meta-analysis

Abstract: BackgroundDementia is a clinical syndrome commonly seen in the elderly individuals. With the prevalence of dementia, the incidence of neuropsychiatric symptoms in dementia patients is increasing annually. Agitation, as one of the neuropsychiatric symptoms, has a serious impact on the quality of life of patients with dementia. Several antidepressant drugs have been shown to be effective for treating agitated behavior symptoms in patients with dementia, but there are no direct comparisons among those drugs. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Moreover, various forms of carnitine, such as LC (L-carnitine), L-acetyl carnitine (LAC), or a combination of both (LAC and LC), have been shown to enhance sperm motility. Additionally, a recent network meta-analysis study found that zinc as an ~ 17 ~ antioxidant in supplementation improves sperm quality parameters in infertile men [23] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, various forms of carnitine, such as LC (L-carnitine), L-acetyl carnitine (LAC), or a combination of both (LAC and LC), have been shown to enhance sperm motility. Additionally, a recent network meta-analysis study found that zinc as an ~ 17 ~ antioxidant in supplementation improves sperm quality parameters in infertile men [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The global inconsistency by comparing the deviance information criterion (DIC) of the random-effect or fixed-effect model and the DIC less than 11 indicated better global consistency (29). Since all comparisons were monoclonal antibodies versus placebo or different drug dosages, and there was a lack of direct comparison of different monoclonal antibodies and no closed loops in the network plots, the node-splitting method examined the consistency was not performed (30). Besides, we performed heterogeneity analysis for each outcome in our NMA, and sensitivity analyses were further performed by excluding possible low evidence or possible high heterogeneity trials to evaluate the robustness of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review published in March 2023 studied the efficacy of commonly used drugs to treat anxiety for anxiety in AD in randomized clinical trials against placebos. These studies showed that the efficacy using mirtazapine, sertraline, and trazodone did not result in a statistically significant difference when compared to the placebo (SMD = −0.08; 0.31; and 0.03, respectively) ( Chen et al, 2023 ). However, 5-HT anti-depressants such as Citalopram showed an efficacy of 94.8% (SMD = −0.44, 95% CI = −0.72 to −0.16) when compared to placebo and other anti-depressant drugs ( Albert et al, 2012 ).…”
Section: Clinical Presentations and Management Of Alzheimer’s Disease...mentioning
confidence: 99%